Pembinaan kepada Peserta Program Intensif di Sekolah Tinggi Teologi SAPPI Ciranjang Terkait Lingkungan Hidup - Sihombing, Aeron Frior; Tampubolon, Yohanes Hasiholan; Megawe, Jochibeth; Nurhaeni, Neneng; Warum, Samuel; Viktor, Yulianus (Society : Jurnal Pengabdian Masyarakat, 2023)
PkM within the framework of Progsif 2023 involves several crucial stages. These stages encompass preparation, execution, monitoring, evaluation, and publication. Through these stages, the PkM aims to provide benefits to the community, promote biblical values, and integrate an understanding of religious values into everyday life. The event is scheduled to span five days with a focus on understanding specific biblical texts relevant to themes such as sustainable living, the relationship between humanity and nature, and the importance of environmental preservation. Participants will receive guidance to help them apply these values in their daily lives. Furthermore, it is essential to note that this event also involves ongoing monitoring and evaluation stages. This means that the PkM team will continuously monitor and evaluate the event's progress during its implementation, enabling the identification of areas requiring improvement or adjustment. In summary, Progsif 2023 and its related PkM activities have a clear goal of providing benefits to the community while promoting biblical values, environmental stewardship, and a better understanding of humanity's role in creating a sustainable environment. Overall, this represents a positive step in supporting community engagement centered around religious and environmental principles.